Shortcuts in urban green spaces: An analysis of incidental nature experiences associated with active mobility trips - Liu Yu; Fagerholm Nora; Skov-Petersen Hans; Beery Thomas; Wagner Anne Margrethe; Olafsson Anton Stahl (ELSEVIER GMBH, 2025)
Nature experiences and active mobility both deliver well-being and health benefits but have rarely been investigated together. Conceptualizations of nature experiences largely focus on intention, and the planned motivations for visits. However, nature experiences can also be perceived incidentally, if daily living activities like trips are encouraged towards green spaces. In a public participation GIS (PPGIS) survey of five local districts in Copenhagen, 517 respondents mapped 688 places along their walking or cycling shortcut trips through green spaces. This study investigated what types of green space provide opportunities for such shortcuts, what inci-dental nature experiences can be perceived there and the different responses of pedestrians and cyclists. This study also explored the relation between incidental nature experiences and green space characteristics in the form of tree cover density. Lastly, this study explored whether frequent short trips through green spaces relate to nature connectedness. The results show that public green spaces and urban cemeteries in Copenhagen allow for such shortcut trips. Enjoyment of pleasing views is the most perceived incidental nature experience. Pedestrians are found more prone to experience surprise, inspiration and emotion, while cyclists prefer shortcuts close to water, which they value highly. The study suggests that high tree cover density is key to delivering incidental nature experiences. Furthermore, the study shows that people who make frequent trips through green spaces have higher levels of nature connectedness, indicating that incidental nature experiences during shortcut trips trigger the reconnection of people and nature. The study's results support a synergistic approach to integrating green spaces and active mobility in planning and management practice, where incidental nature experiences should be emphasized.